The Curing Coma Campaign and the Future of Coma Research - Olson, DaiWai M.; Hemphill, J Claude; Provencio, J Javier; Vespa, Paul; Mainali, Shraddha; Polizzotto, Len; Kim, Keri S.; McNett, Molly; Ziai, Wendy; Suarez, Jose I.; the Curing Coma Campaign Collaborators (Seminars in Neurology, 2022)
Recovery from coma or disordered consciousness is a central issue in patients with acute brain injuries such as stroke, trauma, cardiac arrest, and brain infections. Yet, major gaps remain in the scientific underpinnings of coma and this has led to inaccuracy in prognostication and limited interventions for coma recovery. Even so, recent studies have begun to elucidate mechanisms of consciousness early and prolonged after acute brain injury and some pilot interventions have begun to be tested. The importance and scope of this led in 2019 to the development of the Curing Coma Campaign, an initiative of the Neurocritical Care Society designed to provide a platform for scientific collaboration across the patient care continuum and to empower a community for purposes of research, education, implementation science, and advocacy. Seen as a “grand challenge,” the Curing Coma Campaign has developed an infrastructure of scientific working groups and operational modules, along with a 10-year roadmap.
Keywords: coma; disorders of consciousness; endotype; persistent vegetative state; cognitive motor dissociation